High-performance mesoporous γ-Fe2O3 sphere/graphene aerogel composites towards enhanced lithium storage. (20th April 2020) - Liu, Yi-Lin; Yan, Cheng; Wang, Gui-Gen; Li, Fei; Huang-Fu, Jia-Shun; Wu, Bo-Wen; Zhang, Hua-Yu; Han, Jie-Cai
Abstract: Transition metal oxides have recently been demonstrated as highly attractive anodes for high-capacity lithium ion batteries, whose electrochemical properties could be further improved through rational architecture design and incorporating reliable conductive network. Herein, mesoporous γ-Fe2 O3 spheres/graphene aerogel composites were synthesized via a solvothermal pathway followed by suitable annealing. Experimental results reveal the uniform mesoporous structure and well-dispersed γ-Fe2 O3 spheres with the size of 300−400 nm embedded in the mesopores of the graphene aerogel network. Compared with α-Fe2 O3 /graphene aerogel and pure γ-Fe2 O3, the as-synthesized composite delivers, at the first cycle, a high discharging capacity of 1080 mAh g −1 at current density of 200 mA g −1 . Even at much higher current density of 8000 mA g −1, satisfactory discharging capacities of 421.5 mAh g −1 can still be achieved. Upon 100 charging-discharging cycles, the specific capacity of as high as 890.5 mAh g −1 at 200 mA g −1 is maintained. The enhanced electrochemical properties could be attributed to their favorable three-dimensional graphene aerogel network, which accounts for the improved structural stability and electronic conductivity of γ-Fe2 O3 during the lithiation/delithiation process.